Insect Herbivory Releases More Nutrients in Warmer and Drier Forests - Hwang, Bernice C.; Giardina, Christian P.; Barrios-Garcia, M. Noelia; Diao, Haoyu; Duboscq-Carra, Virginia Gisela; Hemp, Andreas; Hemp, Claudia; Jiménez-Castillo, Mylthon; Lobos-Catalán, Paulina; Mumladze, Levan; Palma, Ana C.; Petritan, Ion Catalin; et al. (AMER GEOPHYSICAL UNION, 2025)
Climate, forest successional stage, and soil substrate age can alter herbivore communities and their effects on biogeochemical cycling, but the size and spatial variability of these effects are poorly quantified. To address this knowledge gap, we established a globally distributed network of 50 broadleaved old-growth forests across six continents, encompassing well-constrained local-scale gradients in mean annual temperature (MAT), mean annual precipitation (MAP), succession, and soil substrate age. We used this network to investigate how these variables impact insect foliar herbivory and the associated carbon, nitrogen, phosphorus, and silica fluxes in forest ecosystems. Over 1 to 2 years, we measured stand-level foliar biomass production, leaf-level herbivory, and foliar element concentrations. At the global scale, insect herbivores liberated higher amounts of elements from the canopies of warmer and drier sites than those of cooler and wetter sites with patterns for phosphorus being most pronounced. MAT exerted a stronger influence over insect-mediated element fluxes than MAP. Foliar biomass production and leaf-level herbivory responses to MAT and MAP were mainly responsible for the observed changes in insect-mediated element fluxes; we also observed minor effects of foliar phosphorus concentration on phosphorus fluxes. Local-scale trends were mixed and successional stage or soil substrate age did not appear to influence insect herbivore-mediated element fluxes. These results demonstrate that climate effects on plant-herbivore interactions are stronger at large than small scales, at which herbivory rates and nutrient fluxes appear to be more strongly affected by a diversity of non-climate factors.